Discussions of questions in naval tactics - Makarov, Stepan Osipovich (Classics of sea power, 1990)
As with all the books in the "Classics of Sea Power" series, this book is a key work of professional naval thought. Chosen for its eloquence and timelessness, it provides a depth and understanding that cannot be had from reading secondary sources alone. Makarov's work, published in Russia in 1897 and translated into English in 1898, contains important lessons for modern readers and gives insight into the birth of modern Soviet naval tactics. The introduction to this important theme in naval warfare illustrates how Makarov, by bridging the gap between new technology and old tactics, helped bring the Russian navy into the 20th century. Stephen Osipovich Makarov is considered one of Russia's most brilliant naval theoreticians. A contemporary of Alfred Thayer Mahan's, Makarov took a far more practical approach to the subject of naval tactics and seapower than his American counterpart. He is credited with never losing sight of the pargrammatic applications of his theories and experiments while maintaining a full appreciation of the human dimensions and the need for strong leadership in an increasingly technical age.